Accounting for the collapse of Dick Smith - HUANG, Sterling (Institutional Knowledge at Singapore Management University, 2020)
In August 2019, Oliver Jones, senior manager at the New South Wales Institute of Qualified Accountants, was following the case of the insolvency of Dick Smith Group. The company began when the founder started servicing radios and expanded to carry a wide range of electronics products. Over the years, the competitive consumer electronics industry saw Dick Smith undergo several strategic changes. The founder had sold the company to Woolworths before the supermarket retailer decided to exit the consumer electronics business. After private equity firm Anchorage turned the company around and sold it for a profit in 2014, Dick Smith again experienced financial troubles. Management had bought too much inventory, chose the wrong products to buy and ultimately assumed too much debt during its expansion phase. In 2016, Dick Smith went bankrupt. Subsequently, creditors began litigation against top Dick Smith executives for pursuing a “rebate maximising” strategy that prioritised rebates over customer demand. The auditor was also implicated. While Jones was unsure if the auditor was legally responsible for investor losses, he wondered how they had not found any risks worth flagging. The case study provides students with an opportunity to discuss the importance of proper accounting. Students who have successfully examined the case should be able to analyse financial statements to identify accounts at risk of material misstatement, explain how inventory and working capital management affect a firm’s financial performance and position and understand the accounting treatment for different type of rebates.